Stadia naming rights in sport - Gillooly, Leah; Eddy, Terry; Medway, Dominic (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2022)
This book is an accessible, practical, and systematic guide to stadium naming rights sponsorship within sport, designed to help practitioners and students gain a better understanding of how naming rights work and the benefits that sport and corporate organisations may get from this kind of arrangement. The book explains the key principles underpinning naming rights deals and sports sponsorship in non-specialist language for readers with little prior knowledge of the subject. Drawing on examples and case studies of naming rights sponsorships in international markets, across both professional and amateur sport, the book examines key practical issues such as how naming rights differ from other types of sponsorship, why brands should sign a naming rights deal, and how organisations can maximise their return on naming rights sponsorship. Concise, informative, and practice-focused, this book offers essential insights for all sport management practitioners, for any marketing executives considering sport sponsorship, and for any students or researchers with an interest in sport marketing, sport management, marketing, or events and facilities management.
Introducing naming rights sponsorship -- Why do brands buy naming rights? -- Activating naming rights sponsorships -- Fan reactions to naming rights sponsorship -- Selecting a naming rights partner -- The future of naming rights sponsorship in sport.
OCLC-licensed vendor bibliographic record.
Keywords: Stadiums -- Names; Arenas -- Names; Business names -- Law and legislation; Sports sponsorship -- Law and legislation; BUSINESS & ECONOMICS / Marketing / General